Compliance with Rapid Diagnostic Tests (RDTs) and pre-packaged Artemisinin-based Combination Therapy (ACTs) guidelines among pharmaceutical outlets in Port Harcourt, Nigeria - Nwankwo, Ogechi Kingdom; Ebirim, Chikere Ifeanyi Casmir; Ibe, Sally NO (Archives of Community Medicine and Public Health, 2020)
Background: Malaria remains the major public health problem in Nigeria which accounts for more cases of death in Nigeria than in any other country in the world. It also accounts for 60% of outpatient visits and 30% of hospitalizations among children under 5 years of age in Nigeria. The World Health Organization (WHO) recommends malaria to be tested, track prior to treatment using microscopic blood smear or Rapid Diagnostic Test (RDTs). RDTs are performed within the maximum of five minutes which allows for proper diagnosis and treatment of malaria at all level of health care. The aim of this study is to determine the level compliance with Rapid Diagnostic Tests (RDTs) and pre-packaged Artemisinin-based Combination Therapy (ACTs) guidelines among pharmaceutical outlets in Port Harcourt, Nigeria. Methods: A cross-sectional study design was employed in this study, were 163 dispensing officers of pharmaceutical outlets were recruited through the use of simple random sampling technique of balloting. A structured questionnaire was used for data collection after being validated and its reliability tested. P-value less than 0.05 were considered statistically significant. Results: Of the 160 participants, 80(49.1%) were males, while 83(50.1%) were females. Majority 154(94.5%) of them attained tertiary education, while only 5(3.1%) attained secondary education. Hundred and sixty one (98.8%) of the respondents have heard of RDT and are aware of what it means. Furthermore, 159(97.5%) correctly defined RDT as an acronym for Rapid Diagnostic Test. 159(97.5%) indicated that a positive result is characterized by Double line on the strip which reveal high compliance. Malaria rapid diagnostic testing in pharmaceutical outlets have the potentials to target antimalarial drugs more effectively. Association between Educational attainment of respondent and compliance with RDT used were statistically significant (Chi-square=7.4159. fisher’s exact=0.039; and Chi-square=10.9651, fisher’s exact=0.024 respectively). Conclusion: Pharmaceutical outlets treat malaria but most adhere to the mRDTs and pre-packaged ACTs recommended guidelines while the rest who do not comply opined that signs and symptoms of malaria are easy to recognize hence, they prefer presumptive treatment. There’s need for the government to enforce the recommended guidelines to all hence, would help to reduce over-diagnosis of malaria, over-prescription of anti-malarial drugs, drug resistance and invariably the cost of treatment especially if the testing is done appropriately.